Neurological symptoms in infectious diseases - Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Wójcik, Magdalena; Boreński, Grzegorz; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: In the course of infectious diseases, various neurological symptoms can be observed.The aim of the study: The article focuses on the neurological symptoms presented in infectious diseases.Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed, Google Scholar, ReaserchGate database was carried out using the following keywords: neurological symptoms, infectious diseases, neuropathology.Description: Infectious diseases such as Lyme diseases, syphilis, group A beta-hemolytic Streptoccocus infection, rabies, tetanus, botulism, poliomyelitis, AIDS can be manifested by neurological symptoms. Symptoms that appear as a result of the development of the diseases include these simple, non-specific symptoms such as weakness, abdominal pain, fever or headache to more serious, life-threatening as respiratory failure, arrhythmias. Summary: Many infectious diseases can cause neurological symptoms. It is important to remember about the possibility of these diseases during the diagnostics of neurological conditions.